'Anyone who commits such a cruel crime, must be criminally irresponsible': context effects in forensic psychological assessment. Issue 4 (4th July 2022) - Rassin, Eric
Abstract : In recent years, it has become clear that expert opinion can be biased. It has been argued that forensic psychologists may also be susceptible to bias. In the present study, the vulnerability of forensic psychological evaluation of the suspect's mental health to the context effect (i.e. the influencing of the expert opinion by irrelevant information) was tested. Master students in forensic psychology were asked to interpret test scores of a suspect in a fictitious double murder case. Some participants received a version of the case in which the description of the murders was neutral. Others received a more explicit version. Whereas the explicitness should not affect the forensic psychological evaluation, it was found that participants in the latter condition seemed more concerned about the suspect's mental health than those in the former. It is concluded that training programmes in forensic psychological assessment should devote attention to bias.